Intraoperative electron radiation therapy in retroperitoneal sarcoma - Röder, Falk; Alldinger, Ingo; Uhl, Matthias; Schimmack, Simon; Mechtersheimer, Gunhild; Büchler, Markus W.; Debus, Jürgen; Ulrich, Alexis (International journal of radiation oncology, biology, physics, 2018)
Purpose To report our experience with surgery, intraoperative radiation therapy (IORT), and external beam radiation therapy (EBRT) in retroperitoneal soft-tissue sarcoma. Methods and Materials We conducted a retrospective evaluation of 156 patients (69 primary, 87 recurrent) treated with IORT since 1991. The dominant histology was dedifferentiated liposarcoma (49%); 89% of lesions were high grade. Median tumor size was 11 cm. Surgery resulted in gross complete resection in 92%, and 65% had microscopically positive margins. Median IORT dose was 15 Gy. A total of 114 patients (73%) received additional EBRT (preoperatively n=38, postoperatively n=76, median dose 45 Gy). Results Median follow-up was 38 months (49 months in survivors). The 3- and 5-year local control (LC) rates were 57% and 50%, respectively. On univariate analysis, LC was significantly associated with primary versus recurrent status, histology, grade, Union for International Cancer Control (UICC) stage, resection margin, and addition of EBRT. The 5-year LC was 71% in the primary situation and 79% after R0 resection. On multivariate analysis only disease status, grade, resection margin, and addition of EBRT remained statistically significant. The 3- and 5-year overall survival (OS) rates were 66% and 56%. On univariate analysis, OS was significantly associated with primary versus recurrent status, histology, grade, UICC stage, resection margin, and timing of EBRT. The 5-year OS was 63% in the primary situation and 68% after R0 resection. On multivariate analysis only disease status, grade, and resection margin remained independent prognostic factors. Perioperative mortality was 1%, and major complications occurred in 34% (mainly wound complications). Conclusions Treatment with surgery, IORT, and EBRT is feasible and resulted in good LC and OS, with acceptable morbidity in this unfavorable patient cohort. Incomplete resection and recurrent status resulted in clearly inferior outcomes. Reasonable efforts should be made during primary treatment to prevent the onset of a local recurrence.
Available online 31 October 2017
Gesehen am 24.07.2018